In-service Training, Language Centre, Cyprus University of Technology, Limassol - (:unkn) unknown (My University, 2026)
Prezi Presentation Software Workshop. By Olga Geroghiadou. In-service Training, Language Centre, Cyprus University of Technology, Limassol, Cyprus, June 2011.